Effect of fiber twisting on the Z-directional properties of composites. Issue 23 (December 2022) - Guo, Zitong; Shan, Zhongde; Huang, Ji H; Wang, Dong; Huang, Hao; Chen, Zhe
To further improve the Z-direction tensile properties of flexible oriented 3D braided composites, we proposed a new process for twisting Z-fibers. We found a pattern of increasing and then decreasing tensile strength after twisting fibers with different K-numbers, and the four bundles of 3K fiber with 20 twists/m had the strongest tensile performance, which increased by 29.06% compared with the untwisted. Scanning electron microscopy was used to observe the twisting morphology and hairiness statistics of fiber bundles to analyze the reasons for this phenomenon. In order to increase the theoretical research on twisted fiber bundles, the relationships between the twist of fiber bundles and the tensile strength of fiber bundles, the length of fiber bundles, and the elongation of fiber bundles were established by using the idea of the least square method, and the prediction of fiber bundle strength was realized by twisting, length, and elongation purpose. The geometric model of the twisted fiber bundle was established, and the relationships between axial strain and radial strain of fiber bundles, axial strain and Poisson's ratio were realized. Combined with finite element simulation, the stress distribution position of the twisted fiber bundle was predicted. Finally, combined with the flexible-oriented three-dimensional weaving method, we selected the fiber with a twist of 20 twists/m as the Z-direction fiber, and completed the Z-direction performance enhancement of the composite material and, compared with the untwisted fiber, the tensile strength was increased by 60.9%.